2015
DOI: 10.4067/s0718-221x2015005000040
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the chemical structure and decay resistance of heat-treated narrow-leaved ash wood

Abstract: We analyzed the effects of heat treatment on the chemical structure of wood from narrow-leafed Ash (Fraxinus angustifolia), a fast-growing and economically valuable species. We also analyzed the effects of heat treatment on the wood's resistance to four decay fungi. Narrow-leafed Ash wood samples were heated with saturated steam to 140, 180, 200, and 220°C for 2, 4, and 6 h. The relative contents of extractable components were analyzed, as well as the levels of holocellulose, cellulose, and lignin. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…The increase in resistance also increased with an increasing duration of heat treatment at the higher temperatures. Yalcin and Ibrahim (2015) found good correlations between the reduction in mass loss due to fungal attack and the decrease in equilibrium moisture content and changes in the wood's chemical composition due to heat treatment.…”
Section: Introductionmentioning
confidence: 85%
“…The increase in resistance also increased with an increasing duration of heat treatment at the higher temperatures. Yalcin and Ibrahim (2015) found good correlations between the reduction in mass loss due to fungal attack and the decrease in equilibrium moisture content and changes in the wood's chemical composition due to heat treatment.…”
Section: Introductionmentioning
confidence: 85%
“…The reduction in wood density by heat treatment can occur at lower temperatures (YALCIN; SAHIN, 2015;KASEMSIRI et al, 2012), but the period for which the wood samples were subjected to heat up to 200°C was not enough to degrade their constituents and to reduce their oven-dry density. In addition, temperature that causes reduction of wood density varies according to species (KORKUT, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The literature reports reduction from 6.8% to 55.21% for total volumetric swelling at 180°C and 240°C for E. grandis wood treated during 4 and 8 h (CALONEGO et al 2012). The heat treatment involves the application of temperature between 160°C and 260°C (ESTE-VES; PEREIRA, 2009), combined with other variables, such as time (KESIK et al, 2014;YALCIN;SAHIN, 2015), pH (WANG et al, 2012), presence of atmosphere (CANDELIER et al, 2013;KUZ-MAN et al, 2015) and relative humidity (OUMAROU et al, 2015). This process degrades the hemicellulose and cellulose of the wood (BRITO et al, 2008), limiting moisture adsorption capacity and increasing the wood dimensional stability (AYTIN et al, 2015;BASTANI et al, 2015;ESTEVES et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Higher acidity of heat-treated wood was also reported by Miklečić and Jirouš-Rajković [25] for beech wood (Fagus sylvatica L.) and Pavlič [23] for Scots pine wood (Pinus sylvestris L.). Several studies have shown decrease in the pH of heat-treated wood depends on the heating temperature and time [26,27]. However, Herrera et al [20] reported that acidity values of European ash wood (Fraxinus excelsior L.) decreased with the intensity of treatment (pH increased gradually).…”
Section: Heat-treated Wood As a Substrate For Coatingsmentioning
confidence: 99%